Polysaccharide-Based Nanocomposites for Gene Delivery and Tissue Engineering - Showkat, Ahmad Bhawani (Woodhead Publishing, 2021)
Polysaccharide-Based Nanocomposites for Gene Delivery and Tissue Engineering presents quantitative background on new polysaccharide nanocomposites in a clear and logical way, highlighting the most exciting applications in gene delivery and tissue engineering and their progress. The book focuses on the different types of polysaccharide nanocomposites for gene delivery and tissue engineering and covers polysaccharide hydrogels for tissue engineering and polysaccharide magnetic nanocomposites for gene delivery. Chapters cover various nanocomposites presented in twenty-one separate chapters. This book will be of great interest to all those researching the development and applications of polysaccharide-based nanocomposites for modeling.